PERBEDAAN KETERAMPILAN BERPIKIR KOMPUTASIONAL SISWA KELAS V SD NEGERI 101789 BERDASARKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN PROBLEM POSING - Fifir Irwanti; Abdul Mujib (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Computational thinking is a form of Higher-Order Thinking Skill (HOTS) that assists students in decision-making and problem-solving, while also enhancing their performance in mathematics. This study aims to determine the differences in computational thinking skills among fifth-grade students at SD Negeri 101789 when taught using the Problem-Based Learning model versus the Problem-Posing model. Quantitative research is defined as a method grounded in positivism; it involves studying specific populations or samples—typically selected via random sampling—collecting data through research instruments, and employing quantitative or statistical analysis to test established hypotheses. A population comprises the entire set of objects under study, whether they are people, things, events, values, or occurrences. Based on this definition, the target population for this study consists of all 60 fifth-grade students at SD Negeri 101789, comprising 28 boys and 32 girls. Random sampling was used to assign classes to the two experimental groups: Experiment Group I consisted of 30 students from class V-A (taught using Problem-Based Learning), and Experiment Group II consisted of 30 students from class V-B (taught using Problem-Posing). This study employs an experimental research method, specifically a quasi-experimental design. The hypothesis test analysis presented in the table above reveals a significance value of 0.000 for both the Problem-Posing and Problem-Based Learning methods, indicating a significant difference between the two. Furthermore, a comparison of the calculated t-value (t_{count} = 4.058) against the critical t-value (t_{table}) at df = 58 (2.001) shows that t_{count} > t_{table}. Based on the significance value of 0.000 (< 0.05), it can be concluded that the null hypothesis (H₀) is rejected and the alternative hypothesis (H₁) is accepted; there is a difference in students' understanding of computational thinking skills when using the Problem-Based Learning and Problem-Posing learning models. Results from Experiment I indicate that Problem-Based Learning is highly effective in developing computational thinking skills related to problem-solving. However, students' creativity in formulating problems was not optimally honed, as the problems were provided by the teacher.